Perspectives and Challenges in the Fight Against COVID-19: The Role of Genetic Variability - Guilger-Casagrande, Mariana; de Barros, Cecilia T.; Antunes, Vitória A. N.; de Araujo, Daniele R.; Lima, Renata (Frontiers in Cellular and Infection Microbiology, 2021)
In the last year, the advent of the COVID-19 pandemic brought a new consideration for the multidisciplinary sciences. The unknown mechanisms of infection used by SARS-CoV-2 and the absence of effective antiviral pharmacological therapy, diagnosis methods, and vaccines evoked scientific efforts on the COVID-19 outcome. In general, COVID-19 clinical features are a result of local and systemic inflammatory processes that are enhanced by some preexistent comorbidities, such as diabetes, obesity, cardiovascular, and pulmonary diseases, and biological factors, like gender and age. However, the discrepancies in COVID-19 clinical signs observed among those patients lead to investigations about the critical factors that deeply influence disease severity and death. Herein, we present the viral infection mechanisms and its consequences after blocking the angiotensin-converting enzyme 2 (ACE2) axis in different tissues and the progression of inflammatory and immunological reactions, especially the influence of genetic features on those differential clinical responses. Furthermore, we discuss the role of genotype as an essential indicator of COVID-19 susceptibility, considering the expression profiles, polymorphisms, gene identification, and epigenetic modifications of viral entry factors and their recognition, as well as the infection effects on cell signaling molecule expression, which amplifies disease severity.